2014
DOI: 10.1002/14651858.cd010026.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol versus hypertonic saline for brain relaxation in patients undergoing craniotomy

Abstract: Mannitol versus hypertonic saline for brain relaxation in patients undergoing craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…Recent guidelines suggest the use of HTS as a second-line therapy in cases where mannitol fails to reduce ICP [8]. Despite hyperosmolar solutions being routinely used in neurosurgical and neurocritical care (NCC) patients for brain relaxation and ICP management [8][9][10][11][12][13][14], there is scanty information on the time course of their haemodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent guidelines suggest the use of HTS as a second-line therapy in cases where mannitol fails to reduce ICP [8]. Despite hyperosmolar solutions being routinely used in neurosurgical and neurocritical care (NCC) patients for brain relaxation and ICP management [8][9][10][11][12][13][14], there is scanty information on the time course of their haemodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The first reviewed the use of mannitol or HTS for brain relaxation in patients undergoing craniotomy for elective tumour resection. 12 It included six RCTs with 527 participants, and concluded that HTS significantly reduces the risk of tense brain during craniotomy (relative risk: 0.60; 95% CI: 0.44e0.83). Although not directly comparable to reviews of TBI, it does support the findings of Kamel and colleagues and Mortazavi and colleagues that HTS lowers ICP to a greater degree than mannitol.…”
Section: Pharmacology and Physiology Of Mannitol And Htsmentioning
confidence: 99%
“…Although there was no consensus on the best HS concentration for ICH control, in this study the 3% concentration was used because it was equiosmolar to 20% mannitol. In addition, it has shown good efficacy in intraoperative brain relaxation and in controlling ICH of various causes, with good safety and few side effects 39 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%